Transfer‐Printed Porous Lithium Host with Sulfur Mediated Atomic Tin Clusters for High‐Energy‐Density and Low‐Volume‐Change Lithium Metal Pouch Cells - Zhang, Qiannan; Gu, Xiaokang; Li, Bixuan; Chen, Qian; Zhai, Qingwei; Jin, Chunqiao; Jiao, Yuying; Yang, Weiyang; Zuo, Jinghan; Kang, Peng; Zhao, Zhikun; Zhang, Xiaokun; et al. (Advanced functional materials, 2025)
Carbon based materials have been proved as effective hosts for lithium (Li) metal anode due to their light weight and good conductivity. However, their practical applications are hindered by non‐uniform lithiophilic site distribution and lacking methods to scale up produce carbon/Li composite electrodes. Herein, a buffer layer (≈3 µm) consisting of sulfur‐mediated ultrafine tin clusters uniformly decorated on three‐dimensional carbon (3DC‐SSn) is designed and roll‐to‐roll imprinted onto Li surface, which is scalable for large‐scale fabrication. The sufficient accommodation space of 3D structure and homogeneous distribution of lithiophilic tin clusters significantly reduce local current density and enhance the uniformity of Li nucleation, synergistically alleviating volume change and promoting dense Li deposition. As a result, the 430 Wh kg −1 LiNi 0.8 Co 0.1 Mn 0.1 O 2 .